2005
DOI: 10.1176/appi.ajp.162.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial of Exposure and Ritual Prevention, Clomipramine, and Their Combination in the Treatment of Obsessive-Compulsive Disorder

Abstract: Clomipramine, exposure and ritual prevention, and their combination are all efficacious treatments for OCD. Intensive exposure and ritual prevention may be superior to clomipramine and, by implication, to monotherapy with the other SRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
397
6
22

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 866 publications
(447 citation statements)
references
References 47 publications
22
397
6
22
Order By: Relevance
“…This response rate is quite typical for prior studies of intensive, daily CBT for OCD. [23][24][25] For example, Foa et al 25 also studied OCD patients treated with intensive ERP for 4 weeks. Their intent-to-treat and completer response rates were 62 and 86%, respectively, similar to our response rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This response rate is quite typical for prior studies of intensive, daily CBT for OCD. [23][24][25] For example, Foa et al 25 also studied OCD patients treated with intensive ERP for 4 weeks. Their intent-to-treat and completer response rates were 62 and 86%, respectively, similar to our response rates.…”
Section: Discussionmentioning
confidence: 99%
“…25 Sessions no. 1-3 included a comprehensive behavioral assessment, education for the patient in self-monitoring of obsessions, compulsions and triggers, and a discussion of the rationale and specific goals of CBT for each individual.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In one single-case experimental design intervention, clinicians made some progress, but only after 17 months of intensive behavior therapy (Hartl & Frost, 1999). This disappointing success rate differs markedly from behavioral or pharmacologic treatment of typical OCD cases, such as those involving contamination obsessions and washing compulsions, or doubting obsessions and checking compulsions (Foa et al, 2005). For example, Abramowitz and his colleagues found that only 31% of hoarders exhibited clinically significant improvement, whereas 70% of OCD patients with contamination obsessions did so (Abramowitz, Franklin, Schwartz, & Furr, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We chose this trial for two reasons: 1) in design and sample size, it is typical of psychiatric trials that compare medications and psychotherapy; and 2) because of the paucity of such trials in OCD, the inferences drawn from this specific study are likely to have public health impact. In the original analyses of these data (Foa et al, 2005), MEMs were used to compare outcome, as measured by the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) score (Goodman et al, 1989a;Goodman et al, 1989b). All active treatments were superior to placebo and both EX/RP&CMI and EX/RP, although not different from each other, were superior to CMI.…”
Section: Introductionmentioning
confidence: 99%